Potentiation of excitatory transmission in substantia gelatinosa neurons of rat spinal cord by inhibition of estrogen receptor alpha - Li Kai-Cheng; Zhong Yan-Qing; Zhang Xu (SAGE Publishing, 2010)
Abstract Background It has been shown that estrogen is synthesized in the spinal dorsal horn and plays a role in modulating pain transmission. One of the estrogen receptor (ER) subtypes, estrogen receptor alpha (ERα), is expressed in the spinal laminae I-V, including substantia gelatinosa (SG, lamina II). However, it is unclear how ERs are involved in the modulation of nociceptive transmission. Results In the present study, a selective ERα antagonist, methyl-piperidino-pyrazole (MPP), was used to test the potential functional roles of spinal ERα in the nociceptive transmission. Using the whole-cell patch-clamp technique, we examined the effects of MPP on SG neurons in the dorsal root-attached spinal cord slice prepared from adult rats. We found that MPP increased glutamatergic excitatory postsynaptic currents (EPSCs) evoked by the stimulation of either Aδ- or C-afferent fibers. Further studies showed that MPP treatment dose-dependently increased spontaneous EPSCs frequency in SG neurons, while not affecting the amplitude. In addition, the PKC was involved in the MPP-induced enhancement of synaptic transmission. Conclusions These results suggest that the selective ERα antagonist MPP pre-synaptically facilitates the excitatory synaptic transmission to SG neurons. The nociceptive transmission evoked by Aδ- and C-fiber stimulation could be potentiated by blocking ERα in the spinal neurons. Thus, the spinal estrogen may negatively regulate the nociceptive transmission through the activation of ERα.